Age as the Risk Factor that Affected the Increased Degree of Uterine Prolapse - Shervil Kagayaita Sayko; Eighty Mardiyan Kurniawati; Pudji Lestari (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2018)
Introduction: Uterine prolapse is a gynecological problem that women often experience with a prevalence of 50% and is predicted that the next 30 years will increase by 45% as life expectancy increases. Increased degrees of uterine prolapse have an impact on the deterioration of women's quality of life. The uterine prolapse is influenced by several mutually supportive factors. The purpose of this study was to analyze the relationship between these factors to the degree of uterine prolapse.Methods: This research is an observational analytic research with cross sectional approach. The number of samples were 65 patients with uterine prolapse at Policlinic Gynecology RSUD Dr. Soetomo Surabaya from 2015-2017. Sampling was done by consecutive sampling. To find out the significant level, the collected data will be tested with Fisher Exact Test statistic at significance level α = 0,05.Results: The result showed that there was significant difference between degree of uterine prolapse with age factor (p = 0,016) and obesity (p = 0,041). As for the parity factor (p = 0.508) there was no significant difference between the parity factor and the degree of uterine prolapse.Discussion: Age is a major factor affecting the degree of uterine prolapse, weakening of pelvic floor tissue and muscle in elderly women is the main cause. While on the obesity factor, there is no data to support that obesity is related to the degree of uterine prolapse because the trend indicates that the majority of patients are not obese. In contrast the parity factor, although according to the statistical test there is no difference to the degree of uterine prolapse, the trend shows that parity leads to increased incidence of uterine prolapse itself.Conclusion: Age is a factor that affects the degree of uterine prolapse.